2013
DOI: 10.1177/1091581813497405
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Assessment of a Recombinant Plague Vaccine (rF1V)

Abstract: A recombinant vaccine (rF1V) is being developed to protect adults 18 to 55 years of age from fatal pneumonic plague caused by aerosolized Yersinia pestis. A comprehensive series of studies was conducted to evaluate the general toxicity and local reactogenicity of the rF1V vaccine prior to first use in humans. Toxicity was evaluated in CD-1 mice vaccinated with control material and three dosage concentrations of rF1V with or without Alhydrogel(®) by intramuscular (IM) injection on Study Days 1, 29, 57 and 71 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Confirmation of induction of an active immune response was also included since toxicity linked to components of the immune response induced by the vaccine must also be considered. 20,21,41 -43 The current study provides additional safety data and confirms the utility of the rat model in assessing safety of vaccine candidates using CpG 7909 as an adjuvant.…”
Section: Discussionsupporting
confidence: 67%
“…Confirmation of induction of an active immune response was also included since toxicity linked to components of the immune response induced by the vaccine must also be considered. 20,21,41 -43 The current study provides additional safety data and confirms the utility of the rat model in assessing safety of vaccine candidates using CpG 7909 as an adjuvant.…”
Section: Discussionsupporting
confidence: 67%
“…In the recent past, many reports have been published on F1/LcrV based vaccine formulations. The F1/LcrV vaccine antigens adjuvanted with alum induce robust humoral immune responses and impart 100% protection in a mouse model (16,(21)(22)(23)(24) with no side effects in humans (25). F1/LcrV antigen-based vaccine formulations protect cynomolgus macaques against aerosolized Y. pestis but failed to protect African Green monkeys (26,27).…”
Section: Protection Studiesmentioning
confidence: 99%
“…Neutrophilia was not observed in rabbits injected with aluminum hydroxide and aluminum phosphate adjuvants in contrast to several other adjuvants tested (Destexhe et al ., ). No effects on neutrophils or any other leukocytes were reported in two preclinical safety studies of recombinant protein vaccines formulated with aluminum hydroxide adjuvant (Price et al ., ; Shearer et al ., ). The increase of neutrophils after repeated injections of the vaccine, but not the aluminum adjuvant alone, suggests that this increase is associated with the immune response rather than local inflammation at the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…The acute inflammation in the first few days after injection of aluminum adjuvant or the adjuvanted vaccine in both mice and rabbits is consistent with detailed studies on the kinetics of the inflammatory response at the injection site (Lu & HogenEsch, ). Similar to previous reports, there was no difference in the inflammation observed in the group that received the adjuvant only and the group that received the adjuvanted vaccine suggesting that the local reaction is primarily a response to the aluminum adjuvant (Price et al ., ; Shearer et al ., ). A recent review of repeat dose toxicity studies of vaccines reported a slightly enhanced inflammatory response to adjuvanted vaccines compared with adjuvant only in seven of 12 studies that included both experimental groups, suggesting that the immune response to vaccine antigens can contribute to the inflammation (Baldrick, ).…”
Section: Discussionmentioning
confidence: 99%